(untitled) (The Journal of Geography Education in Africa, 2023)
Quality education in institutions of higher learning is vital in the contemporary world. Although some studies have been conducted on quality education in higher education, no study has focused on the enhancement of quality education through the inclusion of geographical information systems (GIS) as a tool and self-directed learning (SDL) skills in geography teachers’ education where Dewey’s theory of education was applied. This study applies a systematic review to examine the connectivity between teaching through GIS and the enhancement of SDL skills in geography teachers’ education. The study also discusses how the inclusion of GIS and SDL skills in geography teachers’ education at university helps to enhance quality education. Results of studies indicate that there is a connection between GIS, SDL, and the enhancement of quality education in geography teachers’ education. The study thus recommends that GIS and SDL skills should be included in teacher education for student teachers to be productive in society.